Impact of Human Resource Management Practices on Organizational Performance (A Case of Nepal) (The Batuk, 2019)
HRM practices in Nepalese organizations are undergoing continual transition, moving from former personnel concepts to modern HRM policies and strategies. This study focuses on assessing the human resource practices in the manufacturing and service sector institutions in Nepal. This study also attempts to find out the relationship between the adoptions of such practices in their performance. The correlation results suggested that there is negative association between HRM practices and employee turnover whereas there is positive association between HRM practices and productivity. The regression result suggested that there is a negative association between HRM practices and employee turnover whereas there is positive association between HRM practices and productivity. At present many Nepalese business organizations are found using team based job design that fosters the specialization as well as the synergy in the team assignment.